Warhol and Nico: Negotiating Europe from Strip-Tease to Screen Test. (1st October 2016) - Needham, Gary
This article explores Warhol and Nico's relationship with Europe through their formative years and subsequent collaboration in Warhol's underground and experimental filmmaking. In the 1950s Warhol was a commercial artist in New York, circulating in a gay milieu, and his work often conveyed Europe and a European sensibility in its illustration of 'all things Europe', but especially fashion. Nico was a fashion model and frequently seen in European fashion magazines before landing a few film roles, including a small part in La dolce vita (Fellini, 1960) and a featuring role in the French erotic film Strip-Tease (Poitrenaud, 1962). Nico moved to New York and found her way to Warhol's art studio and social scene known as The Factory. At The Factory Nico joined the art-rock group The Velvet Underground at Warhol's insistence and featured in several films Warhol made between 1966 and 1967, including Chelsea Girls (Warhol, 1966) and a number of portrait films called Screen Tests (Warhol, 1964–1966). This article explores the presence and negotiation of Europe in both Nico's and Warhol's life and work in the 1950s and 1960s. The article pays particular attention to their early careers and the shifts in Nico's persona demonstrated by the difference between the French Strip-Tease and Warhol's experimental Screen Tests.